Kerja Layak Bagi Mahasiswa Pekerja Kontrak Paruh Waktu (Garda Depan) Di PT.Aseli Dagadu Djokdja - Disi Riwanda Rabbani (Jurnal Studi Pemuda, 2017)
Globally, the decent work agenda has been promoted by the International Labor Organization (ILO) since 1999 and nowadays stated in the goals number 8 Sustainable Development Goals (SDGs) 2015-2030. At the national level, decent work is the right of all Indonesians as set forth in article 27 UUD 1945. In line with that premise, all workers regardless of their type are entitled to decent work, including college students who work on part-time contracts. The flexible working system on a part-time basis made college students possible to carry on their work and campus activities side by side. PT.Aseli Dagadu Djokdja (PT ADD) is one of the companies in Yogyakarta that employ college students on a part-time contract basis which commonly referred as Garda Depan. Using the conceptual framework of ILO’s decent work, this paper aimed to describe the dynamics of decent work implemented within the company for their part-time workers, which consists of four components: employment, worker’s rights, social security and social dialogue. By using a qualitative method with a descriptive approach, this study concludes that the flexibility of the working system made Garda Depan the vital element of the company. However, their position are vulnerable due to the absence of legal framework for part-time workers making the bargaining position of the company tend to be higher. Thus, the company becomes the main actor in creating a decent work environment, especially in determining decent remuneration, social security and creating rooms for social dialogues.